Understanding innovation platform effectiveness through experiences from west and central Africa. (September 2018) - Davies, Jocelyn; Maru, Yiheyis; Hall, Andy; Abdourhamane, Issoufou Kollo; Adegbidi, Anselme; Carberry, Peter; Dorai, Kumuda; Ennin, Stella Ama; Etwire, Prince Maxwell; McMillan, Larelle; Njoya, Aboubakar; Ouedraogo, Souleymane; et al.
Abstract: Innovation platforms (IPs) are a way of organizing multistakeholder interactions, marshalling ideas, people and resources to address challenges and opportunities embedded in complex settings. The approach has its roots in theories of complexity, the concept of innovation systems and practices of participatory action research. IPs have been widely adopted across Africa and beyond in recent years as a "must have" tool in a range of "for development" modes of agricultural research. Our experiences with establishing and facilitating nine IPs in local settings in west and central Africa contribute to understanding factors that impact on their effectiveness. The nine IPs were variously focused on developing dairy, crop and/or meat value chains by strengthening mixed crop-livestock production systems or seed systems. Using case study methods, we identified variables that contribute to explaining the performance of these IPs in relation to six domains of change in the agricultural system and the sustainability of changes. Thematic analysis was guided by a conceptual framework which grouped variables into four categories (context, structure, conduct, and process) that interact to influence IP performance. Stronger market connections and value chains were generated through some of these IPs but the most prevalent changes overall were in farm productivity and technical knowledge of producers. The structures evolved in some IPs, akin to those of producer collectives, suggested they were filling an institutional gap locally. The effect of the IPs on deeper level institutions that influence agricultural systems and food security was modest, constraining prospects for the IPs to generate impact at scale. Impacts from the IPs on research and development organisations were uncommon but had transformative significance. Our conceptual framework did not offer optimal guidance to understanding how the many variables that contributed to performance of these IPs combined and sequenced, but the pattern of interactions was consistent with increased social capital being the prime mediator for change. Achieving greater prospects for transformational change and impact at scale warrants at least equal attention to three other interconnected change pathways: through markets, institutions and innovation capacity. Important factors for increased impact are individuals and organisations with capacity to purposefully build and manage inter-organisational and cross-scale networks, early diagnostic studies of the institutional landscape, and adaptive processes of critical reflection and learning that continue beyond the short term. Highlights: Stakeholders thought the IPs effective but their outcomes and impacts were modest. Increased social capital was the prime mediator of change. Producer technical knowledge and capacity for collective action were enhanced. Producer-centric approaches and delayed market engagement limited IP impact. R&D actors with orchestration capability are critical for transformative change.